Low Intensity Laser photobiomodulation in the treatment of major aphthous stomatitis – two year follow-up (Research, Society and Development, 2022)
Recurrent aphthous stomatitis (RAS) is one of the most common pathologies in routine dentistry, manifested through necrotizing ulcers that are, in most cases, quite painful and that can last for up to 14 days, affecting the patient's quality of life. Although uncertain, studies indicate that its appearance may be related to the immune system, lack of vitamins, genetic predisposition, among other factors. Its treatment consists of reducing the patient's symptoms and the duration of the lesion in the oral cavity, associated with drugs or therapies that speed up the repair and analgesia process. Low-intensity laser irradiation (LLL) has been used and studied as an auxiliary therapy for RAS. It has, among several pros, analgesic, anti-inflammatory and regenerative effects. The aim of this study was to analyze the effectiveness of LLLT in tissue repair, analgesia and recurrence of recurrent major aphthous lesion in a patient selected from the Hebiatrician at the University of Mogi das Cruzes Dental Clinic followed up since 2019, in which contact length irradiation was performed of an infrared wave of 808nm and a dose around 105J/cm2 in 4 intraoral points, followed by an extraoral application for lymphatic drainage, in two sessions with an interval of 24 hours, with follow-up after 60 days and after 2 years. Using the visual analogue scale (VAS), the patient indicated the intensity and evolution of pain, which was reduced from 10 (severe pain) in the 1st session to 1 (mild pain) in the 2nd session and remained at 0 in the 3rd session. after 60 days and after 2 years. Clinically, the lesion took around 14 days to heal and with irradiation the time decreased to 3 days, with no recurrence after 2 years. LLLT has been shown to be effective in tissue repair, analgesia and recurrence of major aphthous stomatitis lesion for two years, proving to be an effective and reliable treatment.